Tracking foreign capital: The effect of capital inflows on bank lending in the UK - Christiane Kneer; Alexander Raabe (University of Zurich, Department of Economics, 2019)
This paper examines how UK banks channel capital inflows to the individual sectors of the domestic economy and to overseas residents. Information on the source country of foreign capital deposited with UK banks allows us to construct a novel Bartik instrument for capital inflows. Our results suggest that foreign funds boost bank lending to the domestic economy. This result is due to the positive effect of capital inflows on bank lending to non-financial firms and to other domestic financial institutions. Banks do not channel capital inflows directly to households or the public sector. Much of the foreign capital is also channeled back abroad, reflecting the role of the UK as a global financial center.
Keywords: F21; F30; F32; F34; G00; G21; 330; capital flows; bank lending; credit allocation; international finance; instrumental variables; international financial linkages